Study of crude extract yield and gonad maturity level of sea cucumber Phylloporus dobsoni correlation - Sapto Andriyono, ,- (IOP Conference Series: Earth and Environmental Science, 2021)
Abstract. The study of the yield of n-hexane extract on the body wall of Phylloporus dobsoni sp. Is the first research conducted in Indonesia. This study aims to measure the n-hexane extract of the body wall of sea cucumber P. dobsoni which is related to the maturity level of the gonads. The measurement results obtained that the average wet weight and dry weight of sea cucumber body wall was 23.58 grams of body wall wet weight, body wall dry weight 5.56, gonad weight 4.02, and GSI value 18.03. Judging from the histology of male sea cucumber gonads, it is known that they have grown and grown at an advanced stage with an average content of n-hexane extract at an average value of 0.202 grams and 0.266 grams, respectively. Whereas in the female group there are all stages of growth, continued growth, maturity, recovery and post-spawning. The content of n-hexane extract showed an increase in the range of 0.085; 0.2506; 0.278; 0.354 and 0.3045. The increase in extract content in male and female sea cucumbers is possible as a protective mechanism from predation and protection in preserving offspring.